2021
DOI: 10.1002/jctb.6834
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of amaranth RI and fast red E azo dyes by thermophilic Geobacillus thermoleovoransKNG 112

Abstract: BACKGROUND: Accumulation of industrial dyes in wastewater creates not only environmental problems, but also medical and aesthetic problems. Removal of synthetic dyes from contaminated hot textile industrial discharge is a fundamental issue. Herein, the microbial decolorization of azo dyes amaranth RI and fast red E was studied. The decolorization process was studied in terms of various physicochemical and analytical parameters.RESULTS: The azo dye decolorization efficiency was improved with beef extract and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 41 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…In the current study, preliminary screening of DR81 decolorizing mixed bacterial cultures showed that the best decolorization was obtained in the presence of 0.1% yeast extract as it contained essential cofactors for azo bond reduction such as riboflavin to perform the enzymatic reaction [ 39 ]. Moreover, it has been reported that azo dye degradation through azo bond reduction under anoxic conditions requires cofactors, such as NADH or FAD, as they serve as electron donors in the cell [ 3 , 40 ]. Therefore, in the current study, upon increasing yeast extract concentrations to 1%, the decolorization increased within 2 h, in agreement with previous studies [ 2 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, preliminary screening of DR81 decolorizing mixed bacterial cultures showed that the best decolorization was obtained in the presence of 0.1% yeast extract as it contained essential cofactors for azo bond reduction such as riboflavin to perform the enzymatic reaction [ 39 ]. Moreover, it has been reported that azo dye degradation through azo bond reduction under anoxic conditions requires cofactors, such as NADH or FAD, as they serve as electron donors in the cell [ 3 , 40 ]. Therefore, in the current study, upon increasing yeast extract concentrations to 1%, the decolorization increased within 2 h, in agreement with previous studies [ 2 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid industrialization poses a great challenge for the efficient removal of the complex and toxic industrial eco-pollutant wastes, especially dye-contaminated industrial effluents [ 1 , 2 , 3 ]. There are approximately 100,000 known dyes worldwide, with a consumption rate of 10,000 tons/year, and about 5–10% are released in industrial effluent, where azo dyes represent 60% of the used dyes [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of physical modi cation, earthworms dig up tightly packed soils to allow air circulation, which in turn leads to better interaction of oxygen with bacteria and promotes their growth (Lu et al, 2021). Dyes are known to have a negative impact on the germination of plants (Matpang et al, 2017;Rahman et al, 2018;Rajashekarappa et al, 2022). There can be signi cant and direct occupational exposure to malachite green by persons working in textiles, tanneries, or aquaculture farms (Okafoagu et al, 2017;Singh & Chadha, 2016).…”
Section: Introductionmentioning
confidence: 99%